Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.energy.2016.02.145
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of a MnCl2/CaCl2-NH3 two-stage solid sorption freezing system for a refrigerated truck

Abstract: a b s t r a c tA MnCl 2 /CaCl 2 -NH 3 two-stage solid sorption freezing system consisting of a MnCl 2 sorption bed, a CaCl 2 sorption bed, an evaporator and a condenser is established for a refrigerated truck, for which the required refrigerating capacity is 1.13 kW at a refrigerating temperature of À5 C. Composite adsorbents of MnCl 2 and CaCl 2 developed by expanded natural graphite treated with sulfuric acid are utilized. The sorption/desorption process and the resorption process are coupled in the two-stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(6 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Gao et al [59] conducted an experimental study in which they developed and tested a two-stage MnCl 2 /CaCl 2 -NH 3 adsorption system, powered by engine exhaust gases. A light-duty vehicle with an overall thermal transmission coefficient of 0.35 W/(m 2 •K) was considered.…”
Section: Solid Sorption Refrigeration Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gao et al [59] conducted an experimental study in which they developed and tested a two-stage MnCl 2 /CaCl 2 -NH 3 adsorption system, powered by engine exhaust gases. A light-duty vehicle with an overall thermal transmission coefficient of 0.35 W/(m 2 •K) was considered.…”
Section: Solid Sorption Refrigeration Systemsmentioning
confidence: 99%
“…Required refrigerating capacity under different refrigerating temperatures. Reprinted from ref [59]. with permission from Elsevier.…”
mentioning
confidence: 99%
“…There are different classes of thermochemical (sorbents) materials that fit the scope. In the literature, a great number of these thermochemical materials deals with ammoniated [16][17][18][19][20], hydrated salts [21][22][23][24][25] and metal hydrides [26][27][28][29][30][31]. Furthermore, each type of material has its own advantages and shortcomings.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, thermochemical energy materials allow for long-term energy storages as compared to PCMs, which are prone to thermal losses when stored for a long period. To date, metal hydrides, salts (e.g., metal halides) hydrates and ammoniates are the most utilized thermochemical materials for closed sorption systems driven by waste-heat intended for refrigeration [28][29][30][31][32][33][34], heat pumps and transformer applications [34][35][36][37]. The well-accepted layout of these sorption systems is two tanks interconnected, filled with a high temperature (HT) sorbent in one side, and a low temperature (LT) sorbent in the other side.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the integration of the heat recovery system improved the COP by 43% and cooling power by 4%. Gao et al [30] experimentally investigated a two-stage solid sorption freezing system based on the adsorbents pair (two-bed) MnCl 2 -CaCl 2 -NH 3 . The experimental results showed that a maximum refrigerating capacity of 1.25 kW and a coefficient of performance (COP) of 0.143 were obtained in 2 h resorption process at the waste heat and refrigerating temperatures of 230 • C and −5 • C, respectively.…”
Section: Introductionmentioning
confidence: 99%